Virtual Reality in Education - Pragya Nigam Apoorva Asthana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The rapid development of Virtual Reality (VR) and Augmented Reality (AR) technologies has significantly impacted the education sector, offering highly engaging and interactive learning experiences across a variety of fields As VR technology continues to evolve, it has proven to be a powerful tool in addressing traditional challenges in education. By implementing VR, students can engage more deeply with their subjects, leading to enhanced understanding, improved academic performance, and increased student involvement. The existing literature emphasizes VR’s expanding role in improving learning environments, with applications ranging from sports training to advanced simulations in chemical engineering. VR’s ability to replicate dangerous or complex situations has transformed practical education by offering a safe and affordable alternative to physical experiments. In India, studies show encouraging results on VR’s ability to boost student engagement, with numerous institutions beginning to integrate these immersive technologies into their educational programs. The paper also explores the growing influence of emerging trends such as Extended Reality (XR) and the Internet of Everything (IoE) in shaping metaverse-driven educational settings, advancing the frontiers of innovation. Despite the numerous advantages, challenges such as high implementation costs, technological barriers, and the need for adequate training for both educators and students remain. Nonetheless, ongoing research and collaboration indicate that VR will play a key role in the future of education, greatly enhancing learning experiences and outcomes. This review provides valuable insights into VR’s potential to transform educational systems and offers recommendations for its future integration across various educational domains.